Laser powder bed fusion of ultra-high molecular weight polyethylene (UHMWPE) using near-infrared ultrashort laser pulses - Ullsperger, Tobias; Wencke, Yannick L.; Yuerekli, Burak; Matthaeus, Gabor; Rettenmayr, Markus; Luinstra, Gerrit A.; Nolte, Stefan (Materials & Design, 2021)
Laser based additive manufacturing of UHMWPE offers new opportunities for realizing complex components for medical implants. Conventionally, laser powder bed fusion of UHMWPE is achieved by CO2 lasers but up to now the mechanical properties of the produced specimen are still relatively poor. The aim of the presented work is to extend the processing window for this material to improve the physical properties by using ultrashort laser pulses at a wavelength of 1030 nm. The linear absorption of UHMWPE at 1030 nm is extremely low, which prevents the use of common continuous solid-state lasers. By contrast, the 500 fs laser pulses used result in peak intensities of several hundred GW/cm2 leading to multi-photon absorption processes. We show that the absorption can be locally increased up to 20 %. Hence, it was possible to deposit and accumulate enough heat to fuse the polymer particles by controlling pulse energy and repetition rate. A suitable processing regime for sintering and complete melting has been investigated and correlated with the crystallinity and micro-hardness, reaching values similar to molded UHMWPE. Finally, preliminary tensile tests on produced specimens reveal an ultimate tensile strength of 4 MPa, surpassing the values obtained using a CO2 laser.
CRIS-Team Scopus Importer:2023-04-20
Keywords: Additive manufacturing; Laser powder bed fusion; Nonlinear absorption; Polymer sintering; UHMWPE; Ultrashort laser pulses